Effect of hydroxyacetic acid on the water resistance of magnesium oxychloride cement. (20th June 2020) - Luo, Xueru; Fan, Wenqiang; Li, Chunqing; Wang, Yong; Yang, Hongjian; Liu, Xiaoli; Yang, Shaoming
Highlights: Magnesium oxychloride cement was modified by different amounts of hydroxyacetic acid. Hydroxyacetic acid prolongs the setting time, and significantly improves the water resistance. Hydroxyacetic acid can significantly stabilize 5 Mg(OH)2 ·MgCl2 ·8H2 O in water and inhibit the formation of the Mg(OH)2 . Abstract: Magnesium oxychloride cement (MOC) possesses many favorable traits, such as, high mechanical strength, fire resistance and light-weight. However, widespread application has been limited by its poor water resistance, which can be improved by doping with organic acid. In this work, the favorable effects of hydroxyacetic acid (HA) on the water resistance of MOC has been investigated in detail. The result in this study revealed that HA-modified MOC has negligible effects on compressive strength, but can significantly improve the softening coefficient. The phase composition, thermal stability, chemical construction and microstructure of the hydrated products were analyzed by X-Ray Diffraction (XRD), Thermogravimetric-Differential Scanning Calorimetry (TG-DSC), Fourier-Transform Infrared Spectroscopy (FT-IR) and X-Ray Photoelectron Spectroscopy (XPS), and Scanning Electron Microscope (SEM), respectively. The results further show that the high water resistance of MOC can be attributed to HA that formed magnesium hydroxyacetate chelate and inhibited the formation of the Mg(OH)2 . As a result, it significantly stabilized 5Mg(OH)2 ·MgCl2 ·8H2 O in water via the coordination and absorption effect.